The potential in reviving waqf through crowdfunding technology: the case study of Thailand - Mohd. Zain, Nor Razinah; Mahadi, Nur Farhah; Mohd Noor, Azman (IIUM Press, International Islamic University Malaysia, 2019)
Disruption of technology continues to change the global market and economy today. Simultaneously, Islamic social finance and its mechanisms has continued to gain spotlights due to their viability and sustainability nature. They are not only offering chances to achieve Sustainable Development Goals (SDGs) but also beyond such goals. Looking into the application of waqf as one of Islamic social finance's instruments, this continuous charitable giving is preferred due to its features that are perpetual, irrevocable, and inalienable. In Thailand, reviving and sustaining waqf properties are still limited due to the lack of funds. However, with the existence of new technology called crowdfunding platform, the revival of waqf can be made possible. Such revival of waqf is essential for the society at large, especially for the Muslim community. The revival of waqf may provide essential assistance in alleviating poverty and gives an equal opportunity for economic participation. By using a qualitative research method and documentary-based legal analysis, this research looks at the opportunity of reviving waqf in Thailand through crowdfunding platforms.